Evaluation Of Tax Management On Income Tax In The Era Of Digital Transformation Of The Directorate General Of Taxes (Case Study At PT Xyz) - Anthony Pratama; Siti Nuryanah (UNIVED Press, 2026)
Fulfillment of income tax obligations in Indonesia has continued to develop since 2015 until now. This began with the tax authorities' efforts to transform services into digital-based ones with the aim of improving the quality of services and supervision of taxpayer compliance. The DJP application was originally desktop client-based, then developed into a website-based e-Bupot PPh 23/26, then updated to e-Bupot Unification according to PER-24/PJ/2021, and the latest one currently uses Coretax as of January 1, 2025 according to PMK 81/2024. Digital transformation in the taxation system is expected to provide various benefits, such as increasing the tax ratio, reducing tax avoidance and evasion, and encouraging taxpayer compliance. The evaluation was carried out to determine the effectiveness of the company's digital supporting system and the influence of the DJP digital application on the fulfillment of the company's income tax obligations and management during 2021 to 2023. The evaluation process is linked to the potential compliance costs borne by PT XYZ when carrying out its tax management from the planning, organizing, implementing and controlling stages. Through a qualitative method with a case study approach, this study uses triangulation by examining documents related to PT XYZ's Income Tax and analyzing interviews with sources related to PT XYZ's income tax management. The results of this study indicate that PT XYZ has implemented tax management for the implementation of its obligations and rights related to income tax properly. However, PT XYZ can improve the efficiency and effectiveness of its tax management by creating written Standard Operating Procedures and implementing recommendations in order to minimize requests for changes to the contents of withholding evidence and overcome invalid withholding evidence. This study provides a practical contribution to companies in good withholding tax management so that companies can grow faster and more sustainably.